A Marxist Analysis of Social Inequality in the Netflix Series Arcane Season 2 - Dilla Loanda Putri Gaotami; Putri Rindu Kinasih (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study examines the representation of social inequality and class dynamics in the second season of the Netflix animated series Arcane: League of Legends. While previous research has focused on semiotic signs or isolated character dynamics in Season 1, this study explores how structural class conflict operates across the narrative climax of Season 2. Employing a qualitative textual analysis grounded in Karl Marx’s critical framework, the research analyzes specific visual, spatial, and dialogic data across all nine episodes (370 minutes). The findings reveal that the bourgeoisie is represented not only by Piltover’s governing elite, who monopolize technological production (Hextech) and institutional power, but also by Zaun’s Chem-Barons, who function as an extralegal local bourgeoisie exploiting forced child labor. Conversely, the proletariat is embodied by Zaun’s working class, whose material deprivation, addiction, and lack of political autonomy reflect structural alienation. Furthermore, the socio-spatial disparity between Piltover’s refined infrastructure and Zaun’s environmental degradation illustrates how systemic inequality offloads material risks onto marginalized populations. Ultimately, this study demonstrates that Arcane Season 2 presents social inequality not as a series of isolated misfortunes, but as an institutionalized system maintained through state apparatuses, ideological dehumanization, and resource monopoly.